Biological Marker Fingerprints of Crude Oils from Three Oilfields in the Central Niger Delta: Implication to Source Input, Conditions of Deposition, and Thermal Maturation - ANYANWU, Timothy Chibuike; AGBI, Ifeoma Ogeri; TAKYI, Botwe; NJOKU, Joy Obiageli; UGBAJA, Uduak Anthony (GeoScience Engineering, 2022)
Crude oil samples recovered from three oilfields distributed within the central Niger Delta were used to investigate biological marker fingerprints, sources of organic matter, conditions of deposition, and thermal maturation. This was achieved by the application of gas chromatography-mass spectrometric (GC-MS) analyses on the saturated components of the crude oils. The biological marker ratios show low sterane/hopane (steranes/hopane ˂ 1) in the scope of 0.29 to 0.61 indicating that the crude oils initiated from rocks containing high terrigenous biota (mainly land plants). The n-alkanes distribution and the pristane/phytane ratios (0.63 to 2.08) suggested source deposition under oxic to suboxic environmental conditions. The percentage composition of C27, C28, and C29 steranes and oleanane index (18α (H)-oleanane/ C30 17α (H)-hopane) also indicated major contributions from terrigenous organic biota with minor marine source input. The studied crude oils have C32:22S/ (22S+22R) ratios in the scope of 0.55 to 0.64, and these values suggested high maturation level. This agrees with the oleanane index (0.64 to 0.95), CPI (0.92 to 1.06), C29: 20S/ (20S + 20R) sterane ratios (0.29 to 0. 61), Ts/(Ts+Tm) ratio (0.45 to 0.83) and moretane/C30 hopane proportion (0.16 to 0.24). Keywords: Biological marker; Depositional conditions; Niger Delta; Organic matter; Thermal maturation.